2021
DOI: 10.1016/j.stem.2021.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Regional identity of human neural stem cells determines oncogenic responses to histone H3.3 mutants

Abstract: Highlights d Engineering of human cellular models of H3.3 mutant pHGGs d Regional identity provides competence for mutant H3.3 responses that mirrors pHGG d H3.3-G34R reinforces pre-existing forebrain progenitor transcriptional circuits d G34R mutation disrupts binding of the transcriptional repressor ZMYND11 to H3.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 84 publications
2
50
0
Order By: Relevance
“…We therefore reasoned that human NSCs derived from the fetal hindbrain would represent a developmentally relevant model to investigate the role of H3.3-K27M. Supporting this, we recently demonstrated that human fetal hindbrain NSC cultures recapitulate defining transcriptional features of primary K27M-mutant tumors and, as opposed to forebrainderived NSCs, are sensitized to H3.3-K27M oncogenic activity 29 . Therefore, we used this model to dissect the transcriptional and epigenomic consequences of H3.3-K27M during early stages of gliomagenesis by stably expressing epitope-tagged H3.3 (wildtype or K27M) in hindbrain NSC cultures from two independent human fetal specimens (GCGR-NS19 and GCGR-NS13; see Methods) (Fig.…”
Section: An Isogenic Human Hindbrain Nsc Model Of K27m Mutant Diseasementioning
confidence: 95%
See 1 more Smart Citation
“…We therefore reasoned that human NSCs derived from the fetal hindbrain would represent a developmentally relevant model to investigate the role of H3.3-K27M. Supporting this, we recently demonstrated that human fetal hindbrain NSC cultures recapitulate defining transcriptional features of primary K27M-mutant tumors and, as opposed to forebrainderived NSCs, are sensitized to H3.3-K27M oncogenic activity 29 . Therefore, we used this model to dissect the transcriptional and epigenomic consequences of H3.3-K27M during early stages of gliomagenesis by stably expressing epitope-tagged H3.3 (wildtype or K27M) in hindbrain NSC cultures from two independent human fetal specimens (GCGR-NS19 and GCGR-NS13; see Methods) (Fig.…”
Section: An Isogenic Human Hindbrain Nsc Model Of K27m Mutant Diseasementioning
confidence: 95%
“…Human GCGR-NS19 and GCGR-NS13 cell lines were provided by the Glioma Genetics Resource (www.gcgr.org.uk). The cell lines were derived from the brainstem region of 19-and 13.5-week-old human fetuses, respectively, as previously described 29 Technologies), 20 ng/ml human EGF, 20 ng/ml human bFGF, 10 ng/ml human PDGF-AA, 10 ng/ml human PDGF-BB (all from Peprotech), 5 IU/ml heparin (Sigma) and Laminin-1 (R&D Systems, 2-4 μg/ml).…”
Section: Cell Culturementioning
confidence: 99%
“…Analysis of comprehensive single‐cell transcriptomic atlases of the developing brain and experimentally induced loss in specific cell types may also reveal the cell types, developmental periods and brain regions that are most susceptible to epigenetic perturbation causing brain tumours. The rare cancers driven by H3 mutations are likely intimately linked with restricted developmental contexts and cell‐type lineages that are permissive to their chromatin remodelling effects, as also suggested by a recent study [86]. These altered chromatin states may be promoting indefinite progenitor cell renewal, cell proliferation and acquisition of subsequent genetic alterations, ultimately leading to tumour formation.…”
Section: Discussionmentioning
confidence: 84%
“…While this work was processed for submission, highly related findings were reported, using expression of the fusion protein in murine HSPCs to show the importance of Tip60 interaction and downstream histone acetylation for leukemogenesis (Li et al, 2021). Furthermore, the onco-histone mutation H3.3G34R in pediatric high grade glioblastoma has been linked to impaired recruitment of ZMYND11 and its repressor function on highly expressed genes, promoting tumorigenesis by stabilizing expression of key progenitor genes (Bressan et al, 2021), which is a mechanism reminiscent of the one described for the fusion. As mistargeting of the NuA4/TIP60 complex seems to be the main mechanism employed by the ZMYND11-MBTD1 fusion, it can be most interesting to test some specific KAT5/Tip60 HAT inhibitors (Gao et al, 2014) (Coffey et al, 2012) to determine if de novo acetylation at coding regions is indeed the main oncogenic driving force in this specific group of acute myeloid leukemia, as suggested by the parallel study (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that, in immune cells, stimulation-induced H3.3S31 phosphorylation leads to ejection of ZMYND11, allowing rapid transcriptional activation (Armache et al, 2020). Similarly, the H3.3G34R histone mutation linked to pediatric highgrade gliomas is also linked to displacement of ZMYND11 from chromatin (Bressan et al, 2021). MBTD1 (Malignant Brain Tumor Domain-containing protein 1) was originally identified in the Polycomb Group family of proteins because of its 4 MBT domains.…”
Section: Introductionmentioning
confidence: 99%